Activity against SARS-CoV-2 of Various Anionic Disinfectants and Their Complexes with Hydrophobically Modified Chitosan - Ospennikov, A.S.; Kornilaeva, G.V.; Larichev, V.F.; Fedyakina, I.T.; Fu, Lifeng; Chen, Zhuo; Yang, Yangyang; Shibaev, A.V.; Karamov, E.V.; Turgiev, A.S.; Duan, Liping; Liu, W.J.; et al. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The aim of this work was to study virucidal activity against SARS-CoV-2 of several anionic disinfectants, which are antiseptics recommended by the U.S. Environmental Protection Agency (EPA), and to prepare their complexes with hydrophobically modified chitosan active against SARS-CoV-2. Experiments were performed using a clinical isolate of SARS-CoV-2 obtained from a patient in 2020. It was shown that sodium dodecyl benzene sulfonate (SDBS) is already active at rather small concentrations (above 2 mM), which completely deactivate the virus. In the same concentration range, sodium caprylate does not show activity; and sodium lactate is active against SARS-CoV-2 only at much higher concentrations (225 mM). The most effective disinfectant — sodium dodecylbenzene sulfonate — was used to prepare complexes with hydrophobically modified chitosan. It was found that such complexes exhibit antiviral activity at very low concentrations (1.9 mM chitosan monomer units and 0.25 mM SDBS), at which the polymer without surfactant is not active against SARS-CoV-2.
Keywords: anionic disinfectants; SARS-CoV-2; chitosan; hydrophobic modification; polymer/surfactant complexes; sodium dodecyl benzene sulfonate; sodium caprylate; sodium lactate